The critical challenges facing New Zealand's chief executives: implications for management skills. (January 2014) - Hutchison, Ann; Boxall, Peter
<x xml:space="preserve">Abstract</x> This paper reports a 2012 survey of 265 New Zealand chief executives, representing 27% of the nation's largest organisations. It examines their most critical challenges in the current environment, discusses the implications for New Zealand's management skills, and considers how human resource practitioners can support such skill development. The results reveal a complex environment of changing markets and technologies in which the support of stakeholders, including key funders, is more guarded and conditional; in which there is an ongoing war for talent; and in which business models need to be reframed to respond to fast‐paced and ambiguous change. The data suggest three fundamental management skill needs: managing uncertainty and renewal, managing stakeholders and business partners, and managing people and limited resources. Now, more than ever, human resource specialists need to focus on the development of managers, and take part themselves in development processes that bridge internal and external boundaries.